Cellular force measurement for force reflected biomanipulation - Kim, D.-H.; Kim, B.; Yun, S.; Kwon, S. (Proceedings - IEEE International Conference on Robotics and Automation, 2004)
In biological cell manipulations, manual thrust or penetration of injection pipette into single cells is usually performed by a skilled operator, relying on the visual feedback information only. Accurately measuring cellular force is a requirement for minimally invasive cell injection and it is essential in investigating biomechanical properties of cell membranes. We have fabricated an end-effector with microforce sensing capability for bio cell injections using PVDF piezoelectric polymer and measured several mN level injection force for zebrafish egg cell. Experimental results show that the cellular force level is changed as the injection pipette penetrates yolk and chorion sequentially. As well, the experimental setup with haptic interface suggests that a more reliable biomanipulation can be achieved by supplying real-time cellular force feedback to the operator.